Implementing an applied verbal behavior model in classrooms. - Shillingsburg, M. Alice; Frampton, Sarah E.; Juban, Brittany; Weddle, Sarah A.; Silva, Meghan R. (Behavioral Interventions, 2022)
Applied verbal behavior (AVB) is an intervention approach grounded in Skinner's (1957) analysis of verbal behavior. Common components of the AVB approach have been established as evidence‐based, indicating the approach should be progressed into the manualization and implementation phase of research. In the present study, we used an intervention package consisting of computer‐based training, performance and competency‐based training, and in vivo training to promote the use of AVB procedures in 26 classrooms in a nonpublic school serving students with autism. We evaluated the effects of this intervention package on the performance of teacher level staff via a controlled consecutive case series design, nonconcurrent multiple probe design, and aggregate data analysis using inferential statistics. Results showed that staff members demonstrated high levels of fidelity with AVB procedures when working directly with students. Measures of student behavior showed significantly increased engagement with staff members, reduced interfering behavior, and increased rates of manding. These findings have implications for the dissemination of AVB in educational settings.